2003
DOI: 10.1091/mbc.e02-06-0367
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Na+,K+-ATPase Motion and Incorporation into the Plasma Membrane in Response to G Protein–coupled Receptor Signals in Living Cells

Abstract: Dopamine (DA) increases Na+,K+-ATPase activity in lung alveolar epithelial cells. This effect is associated with an increase in Na+,K+-ATPase molecules within the plasma membrane ( Ridge et al., 2002 ). Analysis of Na+,K+-ATPase motion was performed in real-time in alveolar cells stably expressing Na+,K+-ATPase molecules carrying a fluorescent tag (green fluorescent protein) in the α-subunit. The data demonstrate a distinct (random walk) pattern of basal movement of Na+,K+-ATPase–containing vesicles in nontrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 35 publications
6
43
0
Order By: Relevance
“…They observed that dopamine enhanced Na pump mobility towards the PM, except for 'perinuclear' Na pump (see figure 3 in Bertorello et al, 2003). Although the observed perinuclear Na + /K + -ATPase may be adjacent, immobile ER Na pump, it may also simply be enzyme targeted to the NE.…”
Section: Namentioning
confidence: 98%
See 1 more Smart Citation
“…They observed that dopamine enhanced Na pump mobility towards the PM, except for 'perinuclear' Na pump (see figure 3 in Bertorello et al, 2003). Although the observed perinuclear Na + /K + -ATPase may be adjacent, immobile ER Na pump, it may also simply be enzyme targeted to the NE.…”
Section: Namentioning
confidence: 98%
“…In order to study the effects of dopamine on the trafficking of Na pump, Bertorello and co-workers (Bertorello et al, 2003) expressed GFP-tagged a-subunit in A549 cells. They observed that dopamine enhanced Na pump mobility towards the PM, except for 'perinuclear' Na pump (see figure 3 in Bertorello et al, 2003).…”
Section: Namentioning
confidence: 99%
“…It is noteworthy that dynein kinetics after low Vt and high Vt are similar to the kinetics of Na ϩ , K ϩ -ATPase. Cytoplasmatic dynein is an essential component of microtubules, and disruption of the microtubule network has recently been demonstrated to inhibit vesicle motion toward the plasma membrane and prevent a dopamine-induced increase in the Na ϩ , K ϩ -ATPase activity in alveolar epithelial cells (32). This decrease in cytoplasmic dynein could contribute to an impaired ability of the injured ATII cells to augment Na ϩ , K ϩ -ATPase activity and the associated fluid clearance in high-Vt ventilation.…”
Section: Cell Membrane Proteinsmentioning
confidence: 99%
“…We generated an alveolar epithelial cell line that expresses the Na + /K + -ATPase a1-subunit tagged with GFP and, using these cells, we reported that GPCR agonist stimulation increases the directional movement of ATPase-containing vesicles (Bertorello et al, 2003). In the present study, we investigated the role of myosin-V in the recruitment of the Na + /K + -ATPase to the plasma membrane.…”
Section: Introductionmentioning
confidence: 97%